إتجاهات الطلبة نحو العودة لنظام التدريس الحضوري - رفقة ايمان بن بهاز; وسيلة ساسوي; د/- سليم معيزة (جامعة عمار ثليجي الاغواط, 2022)
ملخص: هدفت هذه الدراسة الى التعرف على اتجاهات الطلبة نحو العودة لنظام التدريس القديم (الحضوري)، حيث قمنا بدراسة ميدانية على عينة من طلبة كلية العلوم الانسانية و الاسلامية و الحضارة و كلية العلوم بجامعة عمار ثليجي بالأغواط و وقع اختيارنا على مجموعة من الطلبة بلغ عددهم 100 طالب و طالبة تم اختيارهم بطريقة قصدية و بغرض اختبار صحة التساؤلات اعتمدنا على الاستبيان و الملاحظة البسيطة و الوثائق كأدوات لجمع البيانات و على المنهج الوصفي التحليلي. كما اعتمدنا على اسلوب التحليل الكمي لمعالجة احصائيات و بيانات الدراسة. و توصلت الدراسة الى النتائج التالية: • هناك اتجاهات ايجابية لنظام التدريس الحضوري • هناك اتجاهات سلبية لنظام التدريس الحضوري • أثر التعليم عن بُعد بشكل سلبي على التحصيل الدراسي. الكلمات المفتاحية: اتجاهات، الطلبة، التدريس القديم Summary: This study aimed to idenifiystudents attitudes. To words returing to the old teaching system (attendance), where we conducted a field study on a rample of students from the faculty of humanities Islamic science civilization and the faculty of science of AmmarThelidjiUnuversity of Laghout. We chose a groupe of 100 male and female students they were chosen intentionally and in order to choose the value of the questionnaire, simple observation and documents as too for data collection and for the analytical approach, we all focused and the quantitative analysis method to address the statistics and data of study. The study reached the following results: • Positive trends of the attendance teaching system • Negative trends of the attendance teaching system • Distance education has a negative impact on academic achievement. Key words: trends, students, old teaching
(دراسة ميدانية على عينة من طلبة جامعة عمار ثليجي بالأغواط)